Complex patterns of functional change among TBI survivors from discharge to 6-month follow-up: Findings from a registry-based cohort study - Hosein Kouchaki; Sina Bazmi; Saman Rabiei; Parnia Kamyab; Mohammadreza Khosravi; Reza Taheri; Hosseinali Khalili; Reza Tabrizi (PLoS ONE, 2026)
Background Functional recovery after traumatic brain injury (TBI) is heterogeneous, and reliance on single time-point outcomes may obscure meaningful post-discharge change. Objective To identify early clinical, laboratory, and radiologic factors associated with functional change between hospital discharge and six-month follow-up using the Glasgow Outcome Scale-Extended (GOSE). Methods In this longitudinal study, 2,948 TBI survivors aged 12 years or older admitted to a tertiary trauma center underwent GOSE assessment at discharge and six months post-discharge. Functional trajectories were classified as recovering, stable, or regressing. Multinomial logistic regression evaluated associations between early variables and functional trajectories. Analyses were additionally stratified by discharge GOSE to assess statistical effects. Results Substantial bidirectional functional change occurred after discharge. Several variables, including age, Glasgow Coma Scale, subarachnoid or intraventricular hemorrhage, hemoglobin, and coagulation indices, were associated with both recovery and regression. Discharge GOSE strongly predicted subsequent change but increased the odds of both improvement and decline. Subgroup analyses indicated many unexpected associations reflected ceiling and floor effects and regression to the mean. Nevertheless, some predictors showed consistent directional effects: in non-severe TBI, age 40–74 years, low admission blood glucose, and higher platelet counts; and in severe TBI, age > 40 years, low admission blood glucose, pneumocephalus, and bilateral fixed pupils. Conclusions Post-TBI functional outcomes follow complex, often unpredictable trajectories. These findings highlight limitations of static early prognostication and support a trajectory-oriented approach to post-discharge TBI care.